2014
DOI: 10.1016/j.pain.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Using eye movements to investigate selective attention in chronic daily headache

Abstract: Previous research has demonstrated that chronic pain is associated with biased processing of pain-related information. Most studies have examined this bias by measuring response latencies. The present study extended previous work by recording eye movement behaviour in individuals with chronic headache and in healthy controls while participants viewed a set of images (i.e., facial expressions) from 4 emotion categories (pain, angry, happy, neutral). Biases in initial orienting were assessed from the location of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
77
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 42 publications
12
77
2
1
Order By: Relevance
“…The present results support those obtained with the visual-probe task, suggesting biases for pain-related information are particularly prominent at stimuli presentation times associated with rumination and maintained attention. 1,2 Furthermore, it is notable that the between-group effect size in the present study (ie, d = 0.93) is similar to that reported in a recent visual-scanning task (ie, d = 0.79), 11 and also those reported in pictorial visual-probe tasks (eg, d = 0.71 9 ; d = 0.70 10 ). This indicates that attentional biases are robust features of chronic pain, and that their strength does not diminish despite increased stimuli richness and complexity or task-related cognitive requirements.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The present results support those obtained with the visual-probe task, suggesting biases for pain-related information are particularly prominent at stimuli presentation times associated with rumination and maintained attention. 1,2 Furthermore, it is notable that the between-group effect size in the present study (ie, d = 0.93) is similar to that reported in a recent visual-scanning task (ie, d = 0.79), 11 and also those reported in pictorial visual-probe tasks (eg, d = 0.71 9 ; d = 0.70 10 ). This indicates that attentional biases are robust features of chronic pain, and that their strength does not diminish despite increased stimuli richness and complexity or task-related cognitive requirements.…”
Section: Discussionsupporting
confidence: 85%
“…Although previous studies have found evidence of initial orienting biases in individuals with chronic pain, the flicker task differs to the paradigms adopted in these former studies in terms of task requirements and instructions. Specifically, the visualprobe task 19 required participants to locate a single dotprobe in 1 of 2 possible locations, the visual-scanning task 11 allowed participants to view 4 facial expressions freely, and the visual-search task 12 instructed participants to search for a specific facial expression embedded among 8 faces. The flicker task is the only paradigm which presents participants with complex, real-world scenes and asks them to search for an unspecified disappearing object.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two recent eye-tracking studies using pictorial stimuli, i.e., faces displaying pain and other emotions (Vervoort et al, 2013;Liossi et al, 2014). Vervoort et al (2013) report an initial bias (vigilance) towards pain faces followed by decreasing attentional engagement (avoidance) which was mediated by the level of pain catastrophizing and self-reported pain intensity.…”
Section: Introductionmentioning
confidence: 99%